Co-pyrolysis Characteristics and Synergistic Interaction of Waste Polyethylene Terephthalate and Woody Biomass towards Bio-Oil Production. (26th September 2022) - Anandaram, Harishchander; Srivastava, Bipin Kumar; Vijayakumar, B.; Madhu, P.; Depoures, Melvin Victor; Patil, Pravin P.; Chhabria, Sarika; Patel, Praveen Bhai; Prabhakar, S.
Abstract : In this study, the impacts of co-pyrolyzing wood-based biomass from Ficus benghalensis with PET on liquid oil output, reactivity, and heating values were investigated. The effects of temperature on the product distribution of individual pyrolysis and the biomass-plastic ratio on co-pyrolysis were investigated. For individual pyrolysis, a maximum amount of 40.8 wt (%) liquid oil was obtained from biomass at 450°C. On the other hand, a maximum of 59.5 wt (%) liquid oil was obtained from PET at 500°C. The co-pyrolysis experiments were conducted by blending PET with biomass at different percentages, such as 20%, 40%, 60%, and 80%. At 60% addition of PET, a more positive synergistic effect was identified due to radical secondary reactions. In addition, the physical and chemical characterization studies conducted on pyrolysis oil showed that biomass and plastic materials could be used to make valuable chemicals.